Antifungal properties of substituted 1-phenyl-5-mercaptotetrazoles and their oxidation product, 5-bis-(1-phenyltetrazolyl)disulfide - Nesmĕrák, K; Pospísek, M; Nĕmec, I; Waisser, K; Gabriel, J (Folia microbiologica, 2000)
The antifungal effect of substituted 1-phenyl-5-mercaptotetrazoles was tested with Candida tropicalis, C. pseudotropicalis, C. mogii, Trichosporon cutaneum, Cryptococcus albidus and S. cerevisiae. Candida strains exhibited the lowest sensitivity to the compounds; the most sensitive was S. cerevisiae. The MIC values ranged from 40 to > 1000 mg/mL. The antifungal effect of halogenated compounds decreased in the series of bromo > chloro > fluoro derivatives. The electrochemical oxidation of substituted 1-phenyl-5-mercaptotetrazole derivatives in an acetonitrile medium was studied as a model for the enzymic oxidation of the substance, including study of the effect of water, perchloric and trifluoromethanesulfuric acids on E1/2 and I1. 5-Bis-(1-phenyltetrazolyl)disulfide, the compound with no antifungal effect, has been identified as the main oxidation product of 1-phenyl-5-mercaptotetrazole.
Keywords: acetonitrily; tetrazoly; Chromatography, High Pressure Liquid; Acetonitriles; Antifungal Agents; Fungi; Tetrazoles; Microbial Sensitivity Tests; antifungální látky; houby; elektrolýza; disulfidy; Disulfides; Electrolysis; mikrobiální testy citlivosti; vysokoúčinná kapalinová chromatografie